Leading research in educational administration : a festschrift for Wayne K. Hoy - DiPaola, Michael F., 1947-; Forsyth, Patrick B. (Research and theory in educational administration., 2011)
Leading Research in Educational Administration: A Festschrift for Wayne K. Hoy is the tenth in a series on research and theory dedicated to advancing our understanding of schools through empirical study and theoretical analysis that was initiated by Wayne and Cecil G. Miskel. This tenth anniversary edition honors and celebrates the research leadership Wayne has provided in the field of educational administration through his distinguished career. The festschrift is organized around the analysis of school contexts and includes constructs Wayne and his protégés have studied and researched: climate, trust, efficacy, academic optimism, organizational citizenship, and mindfulness. It concludes with the work of colleagues on the salient contemporary issues of innovation, power, leadership succession, and several others focused on improving schools. Chapter authors all have close connections to Wayne - former students and their students, as well as colleagues and friends.